NARRATIVE PLOT OF THE APOCALYPSE - Jang, Young (Scriptura, 2003)
Since Aristotle, the plot of a narrative has been defined by two characteristics - causality and effects. The fivefold narrative-scheme (namely, constituents of a plot) proposed by Van Dijk, may be very well applicable to the Apocalypse, reflecting the two essential factors of its plot. The narrative plot consists of five phases - "introduction," "setting," "complication," "resolution" and "moral/coda."